Pleiotropic Effects of Atorvastatin Result in a Downregulation of the Carboxypeptidase U System (CPU, TAFIa, CPB2) in a Mouse Model of Advanced Atherosclerosis - Karen Claesen; Lynn Roth; Joachim C. Mertens; Karlijn Hermans; Yani Sim; Dirk Hendriks (MDPI AG, 2021)
Statins (hydroxymethyl-glutaryl-CoA-reductase inhibitors) lower procarboxypeptidase U (proCPU, TAFI, proCPB2). However, it is challenging to prove whether this is a lipid or non-lipid-related pleiotropic effect, since statin treatment decreases cholesterol levels in humans. In apolipoprotein E-deficient mice with a heterozygous mutation in the fibrillin-1 gene (ApoE−/−Fbn1C1039G+/−), a model of advanced atherosclerosis, statins do not lower cholesterol. Consequently, studying cholesterol-independent effects of statins can be achieved more straightforwardly in these mice. Female ApoE −/−Fbn1C1039G+/− mice were fed a Western diet (WD). At week 10 of WD, mice were divided into a WD group (receiving WD only) and a WD + atorvastatin group (receiving 10 mg/kg/day atorvastatin +WD) group. After 15 weeks, blood was collected from the retro-orbital plexus, and the mice were sacrificed. Total plasma cholesterol and C-reactive protein (CRP) were measured with commercially available kits. Plasma proCPU levels were determined with an activity-based assay. Total plasma cholesterol levels were not significantly different between both groups, while proCPU levels were significantly lower in the WD + atorvastatin group. Interestingly proCPU levels correlated with CRP and circulating monocytes. In conclusion, our results confirm that atorvastatin downregulates proCPU levels in ApoE−/−Fbn1C1039G+/− mice on a WD, and evidence was provided that this downregulation is a pleiotropic effect of atorvastatin treatment.